2003
DOI: 10.1080/13636820300200229
|View full text |Cite
|
Sign up to set email alerts
|

Regulation for survival: training and skills in the construction labour market in Jersey, Channel Islands

Abstract: Abstract:There is a crisis in the vocational training provision of the Channel Island of Jersey's construction industry that has similarities with the British situation. Unavailability and inappropriateness of skills, the non-viability of current training and recruitment policies on the island, the fragmentation of the training infrastructure, the demand-driven and task-or job-specific nature of training, the Jersey-born and male focus of recruitment and the uncoordinated, traditional and short-term approach o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…One of respondent stated that: "The organisation I was very small I cannot how I would progress here I then decided to leave" [NCP12]. This result aligns with the finding of Arkani et al (2003) where they observed that a lack of a clear framework for progression for trainees within the organisation would demotivate them from completing the programme. A defined career path would reduce apprentice attrition.…”
Section: No Potentials For Career Progression and Absence Of Mentoringsupporting
confidence: 52%
See 1 more Smart Citation
“…One of respondent stated that: "The organisation I was very small I cannot how I would progress here I then decided to leave" [NCP12]. This result aligns with the finding of Arkani et al (2003) where they observed that a lack of a clear framework for progression for trainees within the organisation would demotivate them from completing the programme. A defined career path would reduce apprentice attrition.…”
Section: No Potentials For Career Progression and Absence Of Mentoringsupporting
confidence: 52%
“…In the UK construction craftspeople apprenticeship programme is typically delivered in 2 to 3 years (Hogarth and Gambin, 2014). This requires an entry-level of a foundation year where students try out numerous trades and will then complete NVQ level 2 in 2 years on day release and level 3 (fully-skilled) in 3 years (Arkani et al, 2003). In comparison, NVQ Level 2 and 3 are the minimum requirements for practising a trade in England and Scotland, respectively (Gordon et al, 2008;Toner 2008).…”
Section: An Overview Of Apprentice Training Programmes In the Ukmentioning
confidence: 99%
“…Licensing is seen as state regulation that protects the public from the incompetent or unscrupulous practitioner, but it could also be understood to be used by occupational groups to restrict entry at the expense of public interest (Zhou, 1993). The definition of licensing ithe context of regulation of the labour market 1s defined in Arkani et al (Arkani et a , l 2003) as "...a set of rules embedded in a structured institutional framework, whether at local or state level that determine, orchestrate or bind reiationships between capiiai and iabour prevailing in a teffitoryn. Kleiner (Kleiner, 2000) and Arkani et al (Arkaniet a , l 2003) both point out that occupational licensing is a set of rules by government which restricts entry to a profession through some demonstration of a minimum degree of competency.…”
Section: Occupational Licensing In the Building Industry And Its Effectsmentioning
confidence: 99%
“…Successful completion of an E d u c a t i o n + T r a i n i n g apprenticeship is essential for running cost-efficient training programmes. A considerable amount of literature has been published on successful completion (Simon and Clarke, 2016;Tichon and Diver, 2010) and non-successful completion (Arkani et al, 2003;Morgan et al, 2008) of apprentice training for craftspeople in the construction sector. However, there has been no comprehensive review of the factors responsible for the success/failure of apprenticeship training programmes.…”
Section: Introductionmentioning
confidence: 99%